2003
DOI: 10.1292/jvms.65.1241
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Enzyme Activities in Plasma and Leukocytes in Dairy and Beef Cattle

Abstract: ABSTRACT. Concentrations of plasma glucose, immunoreactive insulin (IRI) and free fatty acid (FFA) and activities of enzymes related to energy metabolism and lactate dehydrogenase (LDH) isoenzyme pattern in plasma and leukocytes were investigated in lactating Hols tein cows (dairy cattle) and fattening Japanese Black Wagyu x Holstein steers (beef cattle). IRI concentrations and LDH and malate dehydrogenase (MDH) activities in the plasma of beef cattle were significantly higher than those in dairy cattle. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…When used in conjunction with the physical examination the chemistry panel may be useful for establishing initial baseline parameters, formulating a problem or rule out list, planning nutritional options and monitoring the response to it (Russell & Roussel 2007). In fact, in previous studies, plasma metabolite concentrations and the activities of certain enzymes involved in energy metabolism have been shown to be useful indicators of changes in the metabolic status of beef cattle and other animals (Brown et al 2000a, Arai et al 2003, Mori et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…When used in conjunction with the physical examination the chemistry panel may be useful for establishing initial baseline parameters, formulating a problem or rule out list, planning nutritional options and monitoring the response to it (Russell & Roussel 2007). In fact, in previous studies, plasma metabolite concentrations and the activities of certain enzymes involved in energy metabolism have been shown to be useful indicators of changes in the metabolic status of beef cattle and other animals (Brown et al 2000a, Arai et al 2003, Mori et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, LDH-P activity reflects the total activity of LDH, whereas LDH-L activity is considered to reflect mainly the activity of LDH-1 and -2, which convert lactate to pyruvate. The LDH-L/P ratios in plasma and leukocytes in ruminants, which have a dominance of LDH-1, -2 and -3 in their livers, are significantly higher than in dog and cat livers, in which LDH-4 and -5 are dominant (Arai et al, 2003b). LDH isozyme patterns in leukocytes are very close to those in livers of animals (Tanaka et al, 2006).…”
Section: Plasmamentioning
confidence: 73%
“…Plasma (1∼2 ml) was recovered by centrifugation at 4°C and stored at −80°C until use. Peripheral leukocytes were isolated from the buffy coat and washed with cold phosphatebuffered saline (PBS), and cytosolic fractions and mitochondrial fractions were prepared by a method described previously (Arai et al 2003b). …”
Section: Collection Of Blood Samplesmentioning
confidence: 99%
“…On the other hand, plasma lactate dehydrogenase (LDH) isoenzyme patterns which are specific for each animal species, are used as a marker for evaluating metabolic conditions in animals including cattle (Arai et al 2003a;Tanaka et al 2006;Sako et al 2007). Peripheral leukocytes enzyme activities were also a good marker for metabolic conditions of cattle (Arai et al 2003b. It has been reported that stress and nutritional conditions influence cattle immunity (Carroll and Forsberg 2007) and peripheral blood mononuclear cell (PBMC) population change in cattle with different nutritional conditions (Lake et al 2006;Ohtsuka et al 2006b).…”
Section: Introductionmentioning
confidence: 99%